(Gynura pseudochina (Lour.)DC).(Analysis for Pyrolizidine contents in Dried Herbal Tea of Daun Dewa (Gynura pseudochina (Lour.) DC) - Tiurlan Farida Hutajulu; Rahma Sari; Eddy Hartanto (Warta Industri Hasil Pertanian, 2009)
Dewa leaf (Gynura pseudhochina (Lour) DC) often used as herbal tea to its benefit in reducing blood glucose content. One of the active compound in dewa is pyrrolizidine alkaloid. which is active against tumor. The aim of this research was to identify the active compound of pyrrolizidine in leaves of dewa green tea, black tea and dry powder which are resulted from the experiment. The analysis of pyrolizidine was done by quantitative and qualitative methods. The separation method used for the pyrrolizidine compounds was thin layer chromatograpy using methanol:water(85 : 15) as developing solvent. The determination of pyrrolizidine content was done by TLC scanner. The result showed that the RF value of dewa green tea is 0.34 relatively equal to the pyrrolizidine standard (0.360. While the Rf value of pirolyzidine compound in leaves of dewa black tea and dry powder was 0.42 and 0.41 significantly different from pyrrolizidine standard. The pyrrolizidine compound in leaves of dewa black tea and dry powder could not be detected quantitavely by TLC scanner because its concentration was too small, where as in leaf of dewa green tea the pyrrolizidine compound was detected 0.005%. So, it could be concluded that the contents of pyrrolizidine compound in leaf of dewa green tea was higher than pyrrolizidine content in black tea and dry powder of dewa leaf.